O turismo pelas lentes do idoso asilado: um estudo no Asilo Padre Cacique/Porto Alegre-RS - Babinski, Luciana Raquel (My University, 2014)
The fast world population aging process, specially the brazilian, leads to a necessity of attention and studies that contribute to a better comprehension and encourage initiatives that promote a social integration and wellness of the elderly. The tourism, as an alternative of leisure, has shown interest, even still small, in direct their studies to the elderly assistance presenting, usually, as a focus of market segmentation. When focusing the look in the subjects of the tourism , we notice a lack of studies that attempt to these touristic possibilities for old age pensioners, and, usually forgotten by the society. Facing that, this investigation, of qualitative cut, used the told life story of 14 elderly from the old age home Asilo Padre Cacique, in Porto Alegre, to verify if the insertion of leisure and tourism activities in this home can contribute for a better life quality and wellness of their residents, besides of identifying the meaning of tourism for this elderly. The study is presented by a narrative that mentions the story of Miss Odete, a character inspired in the residents life style stories and created as a background to show the discussions about the aging process, the home structure, questions connected to leisure and tourism showing results that evidence the necessity of actions that focus in the human element as the beginning of leisure and tourism practices.
O acelerado envelhecimento populacional mundial, especialmente o brasileiro, remete a necessidade de atenção e estudos que contribuam para melhor compreensão e estímulo de iniciativas que possam promover a integração social e o bem-estar dos idosos. O turismo, enquanto alternativa de lazer, tem demonstrado interesse, ainda que pouco, em direcionar seus estudos ao atendimento de idosos apresentando, normalmente, como foco a segmentação de mercado. Ao se direcionar o olhar nos sujeitos do turismo , verifica-se uma lacuna de estudos que atente as possibilidades turísticas para idosos asilados e, geralmente esquecidos pela sociedade. Diante disso, esta investigação, de corte qualitativo, utilizou a história oral de vida de 14 idosos do Asilo Padre Cacique, em Porto Alegre, para verificar se a inserção de atividades de lazer e turismo neste asilo podem contribuir para a melhoria da qualidade de vida e o bem-estar de seus moradores, além de buscar identificar os sentidos e significados do turismo a estes idosos. O estudo é apresentado por uma narrativa que menciona a história de dona Odete, uma personagem inspirada nas histórias de vida dos idosos do asilo e criada como pano de fundo para apresentar as discussões sobre o processo de envelhecimento; a conjuntura asilar; questões vinculadas ao lazer e ao turismo apresentando resultados que explicitam a necessidade de implantação de ações que focalizem o elemento humano como princípio de práticas turísticas e de lazer.
Keywords: Turismo; Lazer; Velhice; Idosos; Idoso asilado; Leisure; Aging process; Aged; Old age pensioners; Elderly; Tourist trade